2010
DOI: 10.1111/j.1469-8749.2010.03699.x
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in hemiplegic cerebral palsy due to perinatal arterial ischaemic stroke

Abstract: AIM The aim of this study was to describe the frequency, risk factors, manifestations, and outcome of epilepsy in children with hemiplegic cerebral palsy (CP) due to perinatal arterial ischaemic stroke (AIS). METHODThe study group comprised 63 participants (41 males, 22 females) from a populationbased CP register whose brain imaging showed perinatal AIS. Information collected included occurrence of neonatal seizures, family history of epilepsy, motor function and epilepsy onset, treatment, and outcome. Electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 29 publications
2
56
2
1
Order By: Relevance
“…5,37,44 Despite a unilateral lesion, infantile spasms and other epileptic encephalopathies can occur. Fortunately, many children eventually outgrow their epilepsy.…”
Section: Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…5,37,44 Despite a unilateral lesion, infantile spasms and other epileptic encephalopathies can occur. Fortunately, many children eventually outgrow their epilepsy.…”
Section: Epilepsymentioning
confidence: 99%
“…Fortunately, many children eventually outgrow their epilepsy. 44,45 Treatment studies specific to perinatal stroke have not been completed, although they may be excellent epilepsy surgery candidates. The treatment of acute neonatal seizures in perinatal stroke is unstudied, but importantly, continuous electroencephalogram (EEG) monitoring often detects subclinical seizures.…”
Section: Epilepsymentioning
confidence: 99%
“…In 54 children (62%), a physician diagnosis of cerebral palsy was recorded in the medical record. Children who presented with stroke during the neonatal period were more likely to have multiple infarcts (29% vs 3%, p 5 0.001), were younger when they began walking (median age of 13 [IQR 10-17] vs 16 [IQR [13][14][15][16][17][18][19][20][21][22] months, p 5 0.04), and were less likely to have a cerebral palsy diagnosis recorded (50% vs 85%, p 5 0.001) (table e-2). Otherwise, demographics, birth history, and years of follow-up were similar between the 2 groups.…”
mentioning
confidence: 99%
“…4,5,16,17 Among children with delayed presentation of presumed perinatal ischemic stroke, estimates of epilepsy range from 38% to 55%. 18,19 The broad ranges reported across prior studies may be related to modest sample sizes, differences in study setting, varying definitions for epilepsy, or methods of outcome ascertainment.…”
mentioning
confidence: 99%
“…One study reported that symptomatic epilepsy syndromes had lower levels of physical, psychological, and social compared to idiopathic epilepsy syndromes (Sabaz, 2003). Finally, two studies analyzed HRQOL in epilepsy in cerebral palsy and reported decreased levels of functioning and wellbeing in different domains (Wake et al, 2003;Wanigasinghe et al 2010). Finally, four studies reported that there was acceptable agreement between children/adolescents and parents, but parents tended to underestimate the HRQOL of their children (Miller et al, 2003;Van Empelen et al 2005;Yam et al, 2008;Verhey et al, 2009).…”
Section: Health-related Quality Of Life In Children and Adolescents Wmentioning
confidence: 99%